Low‐Temperature Sintering of β‐Spodumene Ceramics Using Li2O–GeO2 as a Sintering Additive. Issue 8 (5th June 2013) - Ogiwara, Toshio; Noda, Yoshimasa; Kimura, Osamu; Reimanis, I.
<x xml:space="preserve">Abstract</x> Low‐temperature sintering of β‐spodumene ceramics with low coefficient of thermal expansion (CTE) was attained using Li2O–GeO2 sintering additive. Single‐phase β‐spodumene ceramics could be synthesized by heat treatment at 1000°C using highly pure and fine amorphous silica, α‐alumina, and lithium carbonate powders mixture via the solid‐state reaction route. The mixture was calcined at 950°C, finely pulverized, compacted, and finally sintered with or without the sintering additive at 800°C–1400°C for 2 h. The relative density reached 98% for the sample sintered with 3 mass% Li2O–GeO2 additive at 1000°C. Its Young's modulus was 167 GPa and flexural strength was 115 MPa. Its CTE (from R.T. to 800°C) was 0.7 × 10−6 K−1 and dielectric constant was 6.8 with loss tangent of 0.9% at 5 MHz. These properties were excellent or comparative compared with those previously reported for the samples sintered at around 1300°C–1400°C via melt‐quenching routes. As a result, β‐spodumene ceramics with single phase and sufficient properties were obtained at about 300°C lower sintering temperature by adding Li2O–GeO2 sintering additive via the conventional solid‐state reaction route. These results suggest that β‐spodumene ceramics sintered with Li2O–GeO2 sintering additive has a potential use as LTCC for multichip modules.